Economies for life in Uruguay: the power of recognition - Rieiro Castiñeira, Anabel; De Giacomi, Brisa; Weisz, Clara Betty; Tommasino Comesaña, Nat (Cooperativismo & Desarrollo, 2024)
The article explores community and solidarity-based economic experiences in Uruguay, emphasizing their connection with care, sustainability, and territorial development. Through participatory workshops and mapping from 2022 to 2024, it identifies practices that prioritize life, collective well-being, and gender equity. It examines three types of work: unpaid domestic labor, informal subsistence activities, and cooperative labor. Women’s central role is highlighted, along with the emergence of solidarity networks developed in response to economic and health crises. Despite their diversity, these initiatives share values such as reciprocity, cooperation, and social justice. The article also notes challenges including fragmentation, the need for political articulation, and improved relations with the state. It concludes that these economic forms offer transformative potential by integrating labor, care, and sustainability into alternative models to traditional economic systems.
Keywords: social economy; solidarity economy; care economy; well-being; social justice; gender equality